Genetic variation and heritability of haploid frailty in maize - Yavuz, Recep; Wang, Hao; Fakude, Mercy; Dermail, Abil; Frei, Ursula Karoline; Liu, Peng; Lübberstedt, Thomas (Frontiers in Plant Science, 2025)
This research investigated the variation in haploid frailty (%HF), which is the difference in trait performance between isogenic haploid and diploid maize lines, and the heritability of haploid frailty for different agronomic traits. A total of 48 isogenic pairs was evaluated in three environments, and 192 isogenic line pairs were evaluated in two environments for plant height (PH), ear height (EH), flag leaf length (FLL) and width (FLW), tassel length (TL), spike length (SL), stem diameter (SD) and tassel branch (TB) number. We found that the qshgd1 locus, associated with spontaneous haploid genome doubling (SHGD), plays a crucial role in improving haploid performance by reducing %HF and promoting diploid-like vigor. The BS39+SHGD genotypes exhibited significantly lower HF% rates compared to the BS39 group, with consistent reductions across multiple traits. Environmental factors also contributed to %HF variation, but genetic influences such as the presence of SHGD proved to have a greater impact on haploid frailty. Leveraging SHGD to enhance both vigor and fertility of haploid plants, is likely to benefit breeding programs in maize and perhaps other crops by more economic and efficient production of DH lines.